Single-cell transcriptomic analysis identified resistant MDSCs and a stress-tolerant gene co-expression network as common MDSC features across multiple disease settings - Chen, Tianmeng; Hughes, Julia; Gregory, Alyssa; Conroy, Julia; Loughran, Patricia; Song, Jinming; Chen, Wei; Billiar, Timothy (Frontiers in Immunology, 2025)
BackgroundMyeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immunosuppressive myeloid cells. The identification of a molecular signature common to MDSC regardless of tissue source would aid in the classification of cells as MDSCs.MethodsSingle-cell RNA sequencing (scRNA-seq) was performed on GM-CSF+ IL-6-induced human MDSCs to characterize the extent of heterogeneity within monocytic MDSCs (M-MDSCs). Cytokine-treated PBMCs were also cultured in the absence of serum to include an additional element of cell stress. Independent published bulk and single-cell transcriptomic datasets were used for validation.FindingsA cluster of cells with preserved MDSC features was induced by the combination of inflammatory signals and cell stress in the form of serum starvation (resistant MDSCs, rMDSCs). A gene co-expression module (the yellow module) was identified specific to rMDSCs. The genes upregulated in MDSCs can be further classified into stress-tolerant vs. -sensitive features. This yellow module mostly contained stress-tolerant genes and showed excellent separation for distinguishing M-MDSCs from control cells across a range of in vitro and in vivo conditions (ROC AUC = 0.954), a feature not found in the stress-sensitive genes. Importantly, rMDSCs were identified in scRNA-seq datasets of immune cells from multiple human cancer types. Tumor C1Q macrophages, which have been associated with immunosuppression, highly expressed the yellow module gene signature.InterpretationThese results demonstrate the importance of the combined roles of inflammation and cellular stress in shaping the features of M-MDSCs and highlight cellular resilience represented by rMDSCs and the role of stress-tolerant features in defining common MDSC features.